Hepatocellular and dermatological outcomes of chlormezanone - Muhammad Zohaib (Journal of the Pakistan Medical Association, 2022)
Madam, Depression is a significantly prevalent mental disorder in our society and is often overlooked, but, medical intervention becomes a necessity in many severe cases. Chlormezanone, a non-benzodiazepine is used to treat depression-related disorders and muscle spasms. However, Chlormezanone is not free of limitations and imperfection; the drug was introduced in 1958 and its use was discontinued in many countries from 1996 on, due to rare but serious cases of toxic epidermal necrolysis1. Chlormezanone has been discontinued in many countries, including the United States, the European Union, South Africa, and Japan. Even then, authorities deemed this drug more beneficial than harmful, and this drug was marketed. However, adding a brief history of events from the introduction to when the toxic effects were first reported and then the discontinuation may be helpful. A study published in 2022 showed how chlormezanone could induce hepatocellular and dermatological toxicity5. Many other reports are showing similar outcomes and a number of case studies have been published in reputable journals regarding the adverse effects of this drug. Studies published by Dubey et al. and Mehboob et al. reported severe dermatoxic drug reactions2,3. These vexatious results support the statement that chlormezanone is not a safe drug to be marketed. The drug has been withdrawn in the US and European Union for about 24 years now but, still being prescribed in many countries including Pakistan during regular practice. Physicians should refrain from prescribing the use of chlormezanone in patients at risk of liver diseases as liver diseases are highly prevalent in Pakistan. A study published in BMJ discussed the lack of trials and inspections in Pakistan to treat anxiety disorders that involve the use of poor drugs and treatment modalities4. Furthermore, people in Pakistan have easy access to all medications and can buy drugs even without a prescription. People in Pakistan are significantly medically unaware and usually take medicines without doctor’s advice on having similar symptoms as before. If patients under the treatment of Chlormezanone experience yellowing of eyes or jaundice-like symptoms and, rashes over the skin, they should seek immediate medical attention. The concerned authorities should also investigate the matter of such drugs and work on implementing drugs with the better risk-benefit ratio in the market.